2022
DOI: 10.55146/ajie.v51i2.27
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Aboriginal tertiary students' perceived experiences of racism and of cultural resilience on educational engagement

Abstract: Racism pervasively impacts the lives of Aboriginal and Torres Strait Islander peoples and is a substantial barrier to accessing, engaging and succeeding within secondary education. Cultural resilience and support have been identified as critical to Aboriginal success within racist institutions. However, research examining experiences of racism and cultural resilience among Aboriginal tertiary students is limited. This study explored the relationship between racism, cultural resilience, and educational engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
0
0
1
Order By: Relevance
“…El análisis de trayectorias educativas de aborígenes australianos, por su parte, ha mostrado que el racismo representa un obstáculo tanto para acceder como para obtener éxito en la educación secundaria, afectando el compromiso académico y la percepción del ambiente de aprendizaje (Gibbs et al, 2022). El panorama es igualmente problemático en educación terciaria, donde existe resistencia a incorporar contenidos culturales indígenas en el currículum tanto de parte de los académicos como de los estudiantes; al respecto, se problematiza la influencia ejercida por los medios de comunicación al tergiversar medidas de reparación y asociarlas a un supuesto trato especial hacia los pueblos indígenas (Grogan et al, 2021).…”
Section: Issn-l: 2027-1786unclassified
“…El análisis de trayectorias educativas de aborígenes australianos, por su parte, ha mostrado que el racismo representa un obstáculo tanto para acceder como para obtener éxito en la educación secundaria, afectando el compromiso académico y la percepción del ambiente de aprendizaje (Gibbs et al, 2022). El panorama es igualmente problemático en educación terciaria, donde existe resistencia a incorporar contenidos culturales indígenas en el currículum tanto de parte de los académicos como de los estudiantes; al respecto, se problematiza la influencia ejercida por los medios de comunicación al tergiversar medidas de reparación y asociarlas a un supuesto trato especial hacia los pueblos indígenas (Grogan et al, 2021).…”
Section: Issn-l: 2027-1786unclassified
“…In Canada, aboriginal students frequently encounter interpersonal discrimination and struggle to feel a sense of belonging on campus (Milne, 2016). In Australia, Gibbs et al (2022) found that experiencing racism in education affects educational engagement and academic outcomes. Similarly, Dovemark's (2013) research in Sweden revealed that indigenous peoples experienced racism in educational settings through private everyday racism and public racism denial.…”
Section: Introductionmentioning
confidence: 99%